Exploration of Mathematical Concept in Kite Making Wau Bengkulu - Sigit, Ego Agus; Syofiana, Mardiah; Risnanosanti, Risnanosanti (Universitas Wiralodra, 2024)
This study aims to analyze the mathematical concepts contained in the making of Wau Bengkulu kites and the exploration of mathematical concepts. This research is descriptive qualitative with ethnographic approach. This research was conducted at a kite-making site located in Suka Raja Village, Kampung Melayu Sub-district, Bengkulu City. The research subjects were kite craftsmen in Bengkulu Province. Data collection methods used were observation, interview, documentation, and literature study. Data analysis techniques were carried out with qualitative analysis techniques, namely, data collection, data reduction, data presentation, and conclusion drawing. The mathematical concepts contained in the making of this traditional game can be utilized to introduce and understand the concept of geometry through local culture. The making of Wau Bengkulu kite shows that there are mathematical concepts contained, namely the concepts of comparison, measurement, volume, folding symmetry and division point.